2015
DOI: 10.1089/jmf.2015.0010
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Intake and Cognitive Decline in Middle-Aged Adults

Abstract: Cognitive decline occurs with age and may be slowed by dietary measures, including increased intake of dietary phytochemicals. However, evidence from large and long-term studies of flavonol intake is limited. Dietary intakes of flavonols were assessed from a large biracial study of 10,041 subjects, aged 45-64, by analysis of a food frequency questionnaire administered at visit 1 of triennial visits. Cognitive function was assessed at visits 2 and 4 with the following three cognitive performance tests: the dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Similarly, Root et al. [32] reported that flavonols intake was associated with preserved cognitive function ( P < .001). A study by Butchart et al.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Similarly, Root et al. [32] reported that flavonols intake was associated with preserved cognitive function ( P < .001). A study by Butchart et al.…”
Section: Resultsmentioning
confidence: 89%
“…The biomarkers included are Aβ40 and Aβ42 accumulations, presence of APOEɛ4 genotype, brain volume, tHcy levels, cerebral blood flow, oxidative stress levels, dental gyrus function, aldehydes malondialdehyde levels [22–28]. Sixteen studies assessed changes in cognition with the use of different cognitive tests, depending on the specific cognitive outcome measured [22,25,29–41]. More information on this is available in the data extraction tables in Appendix D.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations